ANALISIS PERANAN TIM PEMANTAUAN DAN PENGENDALIAN INFLASI DAERAH (TPID) TERHADAP PENGENDALIAN INFLASI DI PROVINSI SUMATERA UTARA - Surya Dharma (Ekonomi dan Keuangan, 2015)
The purpose of this study is to analyze the role of Regional Inflation Monitoring and Regional Controlling Inflation Team (TPID) toward Inflation Restraint (Case Study: North Sumatra Province). This study uses time series data, ie the data is monthly inflation (mounth to mounth) and measured using the Consumer Price Index (CPI) of North Sumatra Province period January 2002 - December 2013. The processing and analysis of data using linier regression model with dummy independent variable and Univariate Autoregressive (AR) time series model using Eviews program. In addition, in analyzing the rate of inflation persistence North Sumatra province conducted a study of sources of inflation persistence and the term back to its natural value. This study found that Regional Inflation Monitoring and Regional Controlling Inflation Team (TPID) have an impact to control the inflation North Sumatra Province. Commodity groups with the highest rate of inflation persistence is the housing, water, electricity, gas and fuel and commodity groups groceries. The study also found that the length of time required by expenditure group to return to its natural value of 3.3 days to 16.15 days.Keywords: Regional Inflation Monitoring and Regional Controlling Team (TPID), Inflation, Inflation Persistence.